Mirror therapy to reduce phantom limb pain. Systematic review - Jesús Sánchez Lozano; Sandra Martínez Pizarro (Acta Médica del Centro)
Introduction: Phantom limb pain is a type of potentially debilitating neuropathic pain that affects 100 million amputees worldwide. The high prevalence, high levels of pain intensity, and associated decreased quality of life force us to explore new avenues to prevent, control, and reverse this condition. In this context, mirror therapy has recently been suggested. Objective: To conduct a review on the effectiveness of mirror therapy to reduce phantom limb pain. Method: A review was carried out following the PRISMA regulations. The databases of PubMed, Cinahl, PsycINFO, SPORTDiscus, Academic Search Complete, Lilacs, IBECS, CENTRAL, SciELO, and WOS were consulted. Results: 71 studies were obtained. After eliminating duplicates and applying the inclusion criteria, 5 clinical trials remained. The sample was 250 patients. The duration of the program ranged from 1-4 weeks. All studies showed safety, and no major side effects occurred. Pain was assessed in all trials although different instruments were used: numerical pain intensity scale, visual analogue scale and brief pain inventory. Conclusions: Mirror therapy is effective in reducing the incidence and intensity of phantom limb pain. This therapy reduces both phantom limb pain and stump pain, improving quality of life and psychological state. This is a method that patients can practice independently, improving self-control. It is safe, economical and easy to use.